2014
DOI: 10.1111/jth.12578
|View full text |Cite
|
Sign up to set email alerts
|

Metformin use decreases the anticoagulant effect of phenprocoumon

Abstract: To cite this article: Wijnen JCF, van de Riet IR, Lijfering WM, van der Meer FJM. Metformin use decreases the anticoagulant effect of phenprocoumon. J Thromb Haemost 2014; 12: 887-90.Summary. Background: Anticoagulant therapy with vitamin K antagonists (VKAs) is affected by interaction of the VKAs with a large number of other drugs. Although metformin is generally not considered to interact with VKAs, we observed a decrease in INR after starting metformin treatment in patients using the VKA phenprocoumon. Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 7 publications
6
12
0
Order By: Relevance
“…Previous studies have focused on the possible drug–drug interaction between phenprocoumon and metformin . The results of both these studies are in agreement with those observed in this study: there is a requirement for a higher dose of VKA due to a weakened effect.…”
Section: Resultssupporting
confidence: 91%
“…Previous studies have focused on the possible drug–drug interaction between phenprocoumon and metformin . The results of both these studies are in agreement with those observed in this study: there is a requirement for a higher dose of VKA due to a weakened effect.…”
Section: Resultssupporting
confidence: 91%
“…Our results suggest that an increase in average bleeding risk is not observed in real-world practice, and are consistent with previous clinical studies that found that sulfonylureas and metformin are associated with reduced INR 18,19 and increased dose requirements of vitamin K antagonists. 18,19,30 Potential mechanisms of a reduced INR include: increased metabolism of vitamin K antagonists by increased liver blood flow by metformin, 30 increased clearance of vitamin K antagonists through increased bile Table S1. g Average daily dose of warfarin and therapeutic drug monitoring for warfarin were adjusted for in sensitivity analyses.…”
Section: Articlesupporting
confidence: 92%
“…salt excretion by metformin, 18,31 reduced hepatic inflammation as a result of antidiabetes drug treatment, which leads to higher expression of CYP enzymes (especially CYP2C9), and increased metabolism of vitamin K antagonists. 19 Although such mechanisms might be expected to increase the risk of thromboembolism if the warfarin dose is not increased in response to a reduction in INR, whether this results in an observable increase in the risk has not yet been studied, but is an important research question.…”
Section: Articlementioning
confidence: 99%
“… We conducted subgroup analyses in strata of (a) age, (b) gender and (c) Charlson comorbidity index. We applied alternative outcome definitions as proxies of ‘metformin intolerance’: (a) failing to fill a second prescription within the first 365 days after index date (up from 180) and (b) failing to fill a second prescription within 180 days but filling a prescription for another antidiabetic drug within the same time window. We applied alternative definitions of exposure to potentially interacting drugs: (a) changing the time window for the drug from 120 prior to index date to 90 and 180 days; (b) requiring another prescription filled within the first 120 days after the index date in addition to the prescription filled prior to the index date; and (c) at least three prescriptions redeemed of the exposure drug within the 2 years prior to the index date and one prescription within the 120 days prior to the index date to ensure chronic use of the exposure drug. If metformin acts as the perpetrator in interactions with other drugs, this might lead to cessation of metformin treatment, which might be misconstrued as metformin intolerance. To assess this, we performed an analysis in which we excluded users of drugs that might be negatively affected by metformin use, namely topiramate (N03AX11) , vitamin K‐antagonists (B01AA) , trospium (G04BD09) and aliskiren (C09XA02) . …”
Section: Methodsmentioning
confidence: 99%
“…4 If metformin acts as the perpetrator in interactions with other drugs, this might lead to cessation of metformin treatment, which might be misconstrued as metformin intolerance. To assess this, we performed an analysis in which we excluded users of drugs that might be negatively affected by metformin use, namely topiramate (N03AX11) [33], vitamin K-antagonists (B01AA) [34][35][36], trospium (G04BD09) [37,38] and aliskiren (C09XA02) [39].…”
Section: Calculations and Statisticsmentioning
confidence: 99%